REVITALISASI MUSIK TRADISIONAL PALEMBANG MELALUI KEGIATAN LOKAKARYA BERBASIS KOMUNITAS DI DEWAN KESENIAN PALEMBANG - Ridatul Jannah; Darwin Effendi; Alpen Saputra; Rani Imelda Syaputri; Vina Mardiana; Putri Rana; Citra Aprilia Andini; Dea Tri Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Traditional music represents an essential component of regional cultural heritage that embodies historical, social, and aesthetic values. However, the rapid advancement of globalization and the dominance of popular culture have contributed to the declining interest of younger generations in traditional music. This article aims to describe community service activities designed to revitalize Palembang traditional music through community-based workshops conducted at the Palembang Arts Council (Dewan Kesenian Palembang/DKP). This study employs a qualitative descriptive method using direct observation, documentation, and literature review. The activities were implemented during the DKP Arts Week and consisted of traditional music workshops, practical instrument-based learning, adaptive performances of traditional songs, and collaborative art presentations. The findings indicate that the workshops enhanced participants’ understanding, appreciation, and engagement with traditional music, strengthened community participation, and supported the regeneration of young traditional musicians. Therefore, community-based workshops serve as an effective strategy for revitalizing traditional music and strengthening local cultural identity in a sustainable manner.